Analisis Kepesertaan Jaminan Sosial Ketenagakerjaan di Usaha Mikro dan Kecil - Saputra, Eka; Amanda Istianah Mutiawati; Langga Langadhy (Pusat Riset dan Inovasi Nasional, 2022)
Social Security employment is one of the government's programs to protect Indonesian workers because this is the mandate of Article 28H paragraph (3) of the 1945 Constitution, after which the government established Law No. 40 of 2004 concerning the National Social Security System and Law No. 24 of 2004 concerning the Social Security Organizing Agency. The regulations mentioned are an active form of the state to protect its people, one of which is from the labor sector. The authors took a study based on some of these rules by taking the title of the analysis of social security participation in employment for micro and small businesses. The formulation of this research problem is 1) what employment social security programs have been followed by job providers in micro and small businesses 2) What factors are the obstacles for job providers in micro and small businesses in participating in the employment social security program. This research is exploratory with a qualitative approach with research objects in small and small businesses, the use of data using primary and secondary data sources. The large number of participants who do not know and participate in BPJS Employment is an obstacle to the lack of participation of BPJS Employment.